Application of Exponential Smoothing Method on Forecasting The Results of Bandeng Pounds in Cot Muda Itam Village-Peureulak District-Aceh Timur: Penerapan Metode Exponential Smoothing pada Peramalan Hasil Tambak Ikan Bandeng di Desa Cot Muda Itam-Kecamatan Peureulak-Aceh Timur - Olivia, Mirda; Erviana, Jumarnis May; Saumi , Fazrina; Elviana, Elviana; Marlinda, Marlinda (Universitas Wiralodra, 2022)
Pould cultivation until now is counted as a bussines that can provide extraordinary income. Cot Muda Itam Village is one of the villages in East Aceh Regency that cultivates ponds by producing milkfish. Milkfish yields also vary, sometimes increasing and not infrequently experience a dcrease in yields.. Therefore, it is necessary to have a study that can predict the production of milkfish un the next harvest. Forecasting is a process of predicting the values of variables based on known values of previously related variables. Based on the results of data processing and data analysis using the linear exponential smoothing method of one brown parameter with and MSE value of 16407,241875 it is obtained that the forecast results in the 11th and 12th months of the harvest decrease, namely 587 kg and 580 kg.